Self-reported long-term needs after stroke. - McKevitt, C; Fudge, N; Redfern, J; Sheldenkar, A; Crichton, S; Rudd, A; Forster, A; Young, J; Nazareth, I; Silver, L; Rothwell, P; Wolfe, C (2011)
BACKGROUND AND PURPOSE: Development of interventions to manage patients with stroke after discharge from the hospital requires estimates of need. This study estimates the prevalence of self-reported need in community-dwelling stroke survivors across the United Kingdom. METHODS: We conducted a survey of stroke survivors 1 to 5 years poststroke recruited through Medical Research Council General Practice Research Framework general practices and 2 population-based stroke registers. Levels and type of need were calculated with comparisons among sociodemographic groups, disability level, and cognitive status using the χ2 test or Fisher exact test, as appropriate. RESULTS: From 1251 participants, response rates were 60% (national sample) and 78% (population registers sample) with few differences in levels of reported need between the 2 samples. Over half (51%) reported no unmet needs; among the remainder, the median number of unmet needs was 3 (range, 1 to 13). Proportions reporting unmet clinical needs ranged from 15% to 59%; 54% reported an unmet need for stroke information; 52% reported reduction in or loss of work activities, significantly more from black ethnic groups (P=0.006); 18% reported a loss in income and 31% an increase in expenses with differences by age, ethnic group, and deprivation score. In multivariable analysis, ethnicity (P=0.032) and disability (P=0.014) were associated with total number of unmet needs. CONCLUSIONS: Multiple long-term clinical and social needs remain unmet long after incident stroke. Higher levels of unmet need were reported by people with disabilities, from ethnic minority groups, and from those living in the most deprived areas. Development and testing of novel methods to meet unmet needs are required.